Blockade of cannabinoid 1 receptor improves glucose responsiveness in pancreatic beta cells - Shin, Hanho; Han, Ji Hye; Yoon, Juhwan; Sim, Hyo Jung; Park, Tae Joo; Yang, Siyoung; Lee, Eun Kyung; Kulkarni, Rohit N.; Egan, Josephine M.; Kim, Wook (Journal of Cellular and Molecular Medicine, 2018)
Cannabinoid 1 receptors (CB1Rs) are expressed in peripheral tissues, including islets of Langerhans, where their function(s) is under scrutiny. Using mouse β-cell lines, human islets and CB1R-null (CB1R−/−) mice, we have now investigated the role of CB1Rs in modulating β-cell function and glucose responsiveness. Synthetic CB1R agonists diminished GLP-1-mediated cAMP accumulation and insulin secretion as well as glucose-stimulated insulin secretion in mouse β-cell lines and human islets. In addition, silencing CB1R in mouse β cells resulted in an increased expression of pro-insulin, glucokinase (GCK) and glucose transporter 2 (GLUT2), but this increase was lost in β cells lacking insulin receptor. Furthermore, CB1R−/− mice had increased pro-insulin, GCK and GLUT2 expression in β cells. Our results suggest that CB1R signalling in pancreatic islets may be harnessed to improve β-cell glucose responsiveness and preserve their function. Thus, our findings further support that blocking peripheral CB1Rs would be beneficial to β-cell function in type 2 diabetes.
Keywords: Animals; Antigens, CD; Cyclic AMP; Diabetes Mellitus, Type 2; Gene Expression Regulation; Glucokinase; Glucose; Glucose Transporter Type 2; Humans; Insulin; Insulin-Secreting Cells; Mice; Receptor, Cannabinoid, CB1; Receptor, Insulin; cannabinoid 1 receptor; glucokinase; glucose transporter 2; insulin secretion; β-cell function